Between Extrapolation and Speculation: Reading Octavia E. Butler in the Geography Classroom. - Müller, Frank I.; Schwarz, Anke (Geographical Journal, 2026)
In this commentary, we explore how the work of Octavia E. Butler, a prominent Black feminist speculative fiction author, can enrich teaching practices aimed at fostering collective and emancipatory forms of future‐making in Political and Urban Geography. Focusing on Butler's Parables duology, a significant example of climate fiction, we demonstrate how fictional narratives of home‐making can shape our understanding of the present and encourage reflection on methods of envisioning the future. We argue that Butler's approach, which combines logical extrapolation with creative speculation, can cultivate transformative practices. This dual and intertwined methodology supports a critical engagement with plausible futures and spatial imaginaries, making it a valuable component of geographical curricula. This commentary explores how the work of Octavia E. Butler may enrich teaching practices aimed at fostering collective and emancipatory forms of future‐making in Political and Urban Geography. Focusing on Butler's Parables duology, we demonstrate how fictional narratives of home‐making can shape our understanding of the present and encourage reflection on methods of envisioning the future. Combining logical extrapolation with creative speculation, Butler's approach supports a critical engagement with plausible futures and spatial imaginaries, making it a valuable component of geographical curricula.